Unleashing The Fire Within: How Harmonious and Obsessive Passion Drive Gen Z Voice - Soerjoatmodjo, Gita Widya Laksmini (Journal of Social and Industrial Psychology, 2025)
Generation Z is increasingly entering the workforce with distinct characteristics, including a strong tendency to express themselves and actively engage within organizations. One form of such engagement is voice behavior, both promotive (offering improvement ideas) and prohibitive (raising concerns about potential risks). This study aims to examine the influence of two forms of work passion—harmonious and obsessive—on both types of voice behavior among Gen Z employees. A total of 400 respondents aged 20 to 30 years, working across various industries in Indonesia, participated in this study. The sample was obtained using incidental sampling, and data were analyzed using simple linear regression to test five direct effect paths. The results showed that all hypotheses were supported. Harmonious passion significantly predicted promotive voice (β = 0.535, p < .001) and prohibitive voice (β = 0.487, p < .001). Obsessive passion also had a significant effect on promotive voice (β = 0.388, p < .001) and prohibitive voice (β = 0.367, p < .001). Furthermore, overall work passion positively influenced voice behavior (β = 0.544, p < .001). These findings suggest that both harmonious and obsessive passions can serve as important drivers of Gen Z’s willingness to speak up in the workplace. This study contributes to the growing literature on youth work psychology and offers practical implications for managing cross-generational human resources.